2021
DOI: 10.1177/0095399721998335
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Islamic Work Ethic and Public Service Motivation

Abstract: The purpose of this article is to examine the differences between public and private sector employees’ public service motivation (PSM) levels and also examine the impact of Islamic work ethic (IWE) as a potential antecedent of PSM in a non-Western setting. This quantitative investigation is based on a sample of 419 employees in 13 public and private organizations in the Kurdistan Region of Iraq (KRI). Independent t test results reveal no statistically significant differences in PSM level between public and pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 93 publications
(136 reference statements)
0
4
0
Order By: Relevance
“…Moreover, previous studies have demonstrated that cultural differences might influence PSM’s prevalence, antecedents, and consequences (Houston, 2011; Rayner et al, 2018). This study provides a contextualized understanding of PSM and responds to the call for more research in non-Western settings (Hassan & Ahmad, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, previous studies have demonstrated that cultural differences might influence PSM’s prevalence, antecedents, and consequences (Houston, 2011; Rayner et al, 2018). This study provides a contextualized understanding of PSM and responds to the call for more research in non-Western settings (Hassan & Ahmad, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…An independent sample T-test was conducted on the three latent variables. According to existing studies, a p -value less than 0.05 means the difference between each variable is significant [ 39 ]. Significant differences were found in the effects of intervention between cities and rural areas in the eastern, central, western and the whole Inner Mongolia, with a p -value of less than 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…The process theory of public service motivation holds that public service motivation is cultivated through the process of socialization ( Moynihan and Pandey, 2007 ), which reflects a series of values, norms, and beliefs ( Perry and Hondeghem, 2008 ). It has been confirmed that the public service systems of various countries imply unique cultural values, and there are different modes and levels of public service motivation in different cultural fields ( Anderfuhren-Biget, 2012 ; Gupta et al, 2020 ), for instance, China ( Lee et al, 2020 ) and Republic of Korea ( Kim, 2009 ; Lee et al, 2020 ) in East Asia under the guidance of Confucian culture, India with ancient civilization ( Gupta et al, 2020 ), Iraq ( Hassan and Ahmad, 2021 ), and Pakistan ( Quratulain et al, 2019 ) under the dominance of Islamic culture, all of which have different public service motivations with different structures and dimensions. No matter from the perspectives of concept, structure or measurement, public service motivation has distinctive cultural characteristics.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%